Current status and prospects of cryopreservation in aquatic crustaceans and other invertebrates. Issue 4 (23rd June 2020) - Guo, Jun-Ho; Weng, Ching-Feng
Abstract: The response of crustaceans and other aquatic invertebrates to low temperatures and the application on cryopreservation has been extensively studied experimentally, which has resulted in the development of techniques that have proven to be valuable. This review addresses cryopreservation protocols for cells such as the general freezing damage caused by pre-treatment, freezing, and thawing as well as important factors that affect the preservation of sperm and embryos of aquatic invertebrates. This review also addresses the short- and long-term effects of low temperature resulting from cryopreservation, as well as a review of the relevant literature on the subject. We discuss specific issues related to the effect of ice crystal formation and freezing time on the survival rates of aquatic species: freezing and thawing rates, toxicity of cryoprotectant concentrations on embryos, osmotic pressure effects on cells, the formation of ice crystals inside and outside of cells, the effects of cryopreservation on development, and the effects of different concentrations of antifreeze protectants.